Pengaruh Kualitas Pelayanan dan Kepuasan Nasabah terhadap Loyalitas Nasabah Pembiayaan KPR di BSI KCP Bandung Buah Batu 3 - Yuli Indriyani; Ahmad Nurkamali; Malik Akbar; Dadang Dimyati (Ma'soem University, 2023)
The background of this research is the lack of service quality on perceived customer satisfaction so that it influence of customer loyalty KPR financing at BSI KCP Bandung Buah Batu 3. This study aims to determine how much influence the quality of service and customer satisfaction on customer loyalty mortgage financing at BSI Bandung Branch Office Buah Batu 3 both partially and simultaneously. The object of research in this report is KPR customers at Bank BSI Sub Branch Office Bandung Buah Batu 3. The type of research is quantitative associative with primary data types and uses data collection techniques in the form of observations, interviews, questionnaires and literature studies. While the sampling technique is non-probability sampling with purposive sampling. The population is all KPR financing customers at BSI Bandung Buah Batu 3 Sub-Branch Office, totaling 87 people with a sample of 47 people. The results showed that there was a significant influence between service quality on customer loyalty in mortgage financing at BSI KCP Bandung Buah Batu 3 is 60,7% with t test results where the value of tcount> ttable (8.331 > 2,412),), that there was a significant influence between customer satisfaction and customer loyalty. KPR financing at BSI KCP Bandung Buah Batu 3 is 39,5% with t test results where the value of tcount> ttable (5,425 > 2,412), and simultaneously there is a significant influence between service quality and customer satisfaction on customer loyalty in mortgage financing at BSI KCP Bandung Buah Batu 3 is 62,2% with the results of the F test where the value of Fcount > Ftable (36,144 > 2,42).